THE INFLUENCE OF PROFITABILITY RATIOS, CAPITAL STRUCTURE AND SHAREHOLDING STRUCTURE AGAINST ON VALUE COMPANY (EMPIRICAL STUDY OF COAL MINING COMPANIES LISTED ON THE STOCK EXCHANGE OF INDONESIA YEAR 2011-2013) - Gilang Ramadhan Fajri; Dwi Asih Surjandari (STIE Binaniaga, 2016)
This study has the objective to assess the